Formulation and characterization of zaleplon buccal disks using grafted Moringa oleifera gum - Sonia Dhiman, Sonika Bhatt, Ashi Mannan, Sandeep Arora, Thakur Gurjeet Singh (Journal of Applied Pharmaceutical Science, 2023)
Natural modified gums act as drug release modifiers in novel drug delivery systems. These modified gums help to alter the physicochemical properties of the drugs. Zaleplon (ZLP) is a pyrazolopyrimidine that is used to treat insomnia. It has a significant problem from a pharmaceutical point of view that it undergoes extensive first-pass hepatic metabolism due to which it has a very short elimination half-life which leads to low bioavailability. The present investigation aimed to study the suitability of grafted Moringa oleifera gum as a mucoadhesive polymer in the formulation of ZLP buccal disks that would allow for pulsatile release via the buccal route, while avoiding extensive hepatic metabolism, increasing bioavailability, and avoiding early morning awakening. The modified M. oleifera gum was prepared using a microwave-assisted graft copolymerization reaction. The optimal calculated concentrations of Moringa gum, ceric ammonium nitrate, and acrylamide were found to be 1.0, 0.1, and 5.0 g, respectively, yielding a graft copolymer with a 65% grafting efficiency. The graft copolymer was further characterized using Fourier transform infrared spectroscopy, X-ray diffraction, differential scanning calorimetry, and scanning electron microscopy. The total ash content, bulk density, angle of repose, Carr’s compressibility index, tapped density, and Hausner’s ratio of naive M. oleifera gum and graft copolymer were determined. The ZLP buccal disks incorporated with gum and graft copolymer were prepared and evaluated for parameters like mucoadhesive strength, mucoadhesive time, and swelling index. The characterization results indicated that the modified Moringa gum exhibited decreased crystallinity and increased surface smoothness. A comparison of buccal disks made of graft copolymer and naive gum revealed that the graft copolymer had a longer ex-vivo mucoadhesion time and a more significant controlled release effect.
Keywords: Buccal disks, mucoadhesive, microwave-assisted, graft copolymer, zaleplon